Surface composition of size-selected sea salt particles under the influence of organic acids studied in situ using synchrotron radiation X-ray photoelectron spectroscopy. Issue 5 (12th August 2022) - Patanen, Minna; Unger, Isaak; Saak, Clara-Magdalena; Gopakumar, Geethanjali; Lexelius, Rebecka; Björneholm, Olle; Salter, Matthew; Zieger, Paul
Abstract : Synchrotron X-ray photoelectron spectroscopic surface characterisation of size-resolved sea salt aerosol particles revealed Mg enrichment in the particle surface layer which was either enhanced or decreased depending on the organic compound added. Abstract : Sea spray aerosols play a key role in the climate system by scattering solar radiation and by serving as cloud condensation nuclei. Despite their importance, the impact of sea spray aerosols on global climate remains highly uncertain. One of the key knowledge gaps in our understanding of sea spray aerosol is the chemical composition of the particle surface, important for various atmospheric chemical processes, as a function of size and bulk composition. Here, we have applied X-ray photoelectron spectroscopy (XPS) to determine the surface composition of both pure inorganic sea salt aerosols and sea salt aerosols spiked with an amino acid (phenylalanine) and a straight chain fatty acid (octanoic acid). Importantly, the use of a differential mobility analyser allowed size-selection of 150, 250 and 350 nm monodisperse aerosol particles for comparison to polydisperse aerosol particles. We observed enrichment of magnesium at the particle surfaces relative to chloride in all aerosols tested, across all particle sizes. Interestingly, the magnitude of this enrichment was dependent on the type of organic present in the solution as well as the particle size. Our results suggest that the observed enrichment in magnesium is an inorganic effect which can be either enhanced or diminished by the addition of organic substances.